Association of Matrix Metalloproteinases and Their Tissue Inhibitor With Disease Activity and Development in Spondyloarthropathy and Inflammatory Bowel Disease - Dursun ELMAS; Ali ŞAHİN and Orhan KÜÇÜKŞAHİN and Nuran TÜRKÇAPAR and Murat TÖRÜNER and Hülya ÇETİNKAYA and Emre KÜLAHÇIOĞLU Alexis K. OKOH and Murat TURGAY (Archives of Rheumatology, 2015)
Objectives: This study aims to investigate whether clinical measures of disease activity and function in ankylosing spondylitis (AS) and inflammatory bowel disease (IBD) are associated with matrix metalloproteinase-3 (MMP-3), matrix metalloproteinase-9 (MMP-9) and tissue inhibitor of matrix metalloproteinase -1 (TIMP-1), and if MMPs can be more useful than C-reactive protein and erythrocyte sedimentation rate in predicting disease activity in AS. Patients and methods: MMP-3, MMP-9 and TIMP-1 levels were measured by ELISA in 20 patients with AS, 20 patients with IBD, 20 patients with IBD and AS (35 males, 25 females; mean age 38.1 years; range 19 to 62 years), and 20 healthy volunteers (10 males, 10 females; median age 38.5 years; range 24 to 63 years) as a control group. Bath Ankylosing Spondylitis Disease Activity Index, Truelove-Witts activity criteria for ulcerative colitis, and Crohn’s Disease of Activity Index scoring systems were used. Results: Highest MMP-3 level was in IBD group (33.51±59.56 ng/mL, p<0.045). MMP-3 levels were significantly higher in patients with IBD and IBD+AS than in patients with AS (p<0.007 and p<0.035, respectively). Highest MMP-9 levels were in the control group (10.35±2.61 ng/mL, p<0.48). MMP-9 levels were higher in AS group patients than those in IBD and IBD+AS groups, but the difference was not statistically significant (p<0.494 and p<0.260, respectively). Highest TIMP-1 levels were in the IBD group (8.11 ng/mL, p<0.006). TIMP-1 levels of IBD group were significantly higher than both AS and IBD+AS groups (p<0.033 and p<0.008, respectively). A statistically significant correlation was detected between serum MMP-3 levels and disease activity and Bath Ankylosing Spondylitis Disease Activity Index score in patients with AS (r=0.841, p<0.05). Conclusion: We concluded that serum MMP-3 levels may be a better biomarker than C-reactive protein and erythrocyte sedimentation rate in showing disease activity in AS.